The effect of prebiotic types on the physical properties of ph and color and organoleptic test of Sumbawa's typical synbiotic cheese - Rizaldi, Lalu Heri; Ariskanopitasari, Ariskanopitasari; Sari, Ratna Nurmalita (Jurnal Agrotek Ummat, 2025)
Sumbawa is known as a cow's milk producing area in West Nusa Tenggara Province. Unfortunately, the use of Sumbawa cow's milk is limited to milk candy products. In fact, the potential for dairy processing is very diverse, one of which is the typical synbiotic cheese product from Sumbawa. This study aims to analyze the effect of prebiotic types on the physical characteristics and organoleptic tests (level of liking) of typical Sumbawa synbiotic cheese products. The physical characteristics tested include pH and color, while the organoleptic test includes taste, aroma, texture and color. This research is experimental in nature by conducting experiments in the laboratory, using a completely randomized design with one factor, namely the type of prebiotic. The types of prebiotics used are uwi flour, seaweed flour and soybean flour. The three types of prebiotics used gave pH test results ranging from 5.82-5.90. The resulting pH value did not have a significant effect on the type of prebiotic used. Analysis of the physical properties of color obtained a range of L values of 76-80, a values of 0-3, b 7-19, Hue 69-90, and ∆E 12.13-3.37 from all treatments. The results of the color analysis showed that all samples were in quadrant one, which indicates that the cheese was yellow with varying intensities. Cheese with prebiotic soy flour is more yellow than prebiotic uwi flour and seaweed. The prebiotic type of cheese product made from yam flour had a significant effect on the color test results, while the organoleptic test results showed that the prebiotic type of yam flour and seaweed flour samples were the most popular in terms of taste, aroma and texture. When compared to the three treatments, cheese made from seaweed flour had the best level of acceptance. The potential for developing synbiotic cheese in the Sumbawa region is very large to produce products that can be accepted by the wider community.